Franco-British-West African research and policy initiatives in West Africa: Relevance to rural development policies - (:unkn) unknown (My University, 2001)
This report presents te results of a number of research programmes funded by the UK Department for International Development (DFID) and the French Ministère des Affaires Etrangères (MAE), with contributions form CORAF/WECARD and the EC. Three franco-british initiatives are presented on land tenure and derived rights, on cocoa policy in West and Central Africa and on research-extension farmer's organisation linkages.
Keywords: African Research